2004
DOI: 10.1007/s11842-004-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling landowner participation in a proposed reforestation loan program

Abstract: The absence of available credit to finance reforestation investments among NIPF landowners has been one of the contributing reasons why landowners do not reforest after harvest. Financial assistance programs are therefore a solution to initiating reforestation investments. However, previous studies indicate many landowners are not actively participating in existing government assistance programs. This paper examines reforestation loans as an alternative financial assistance program. Landowner participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Previous research suggests current or past experience with conservation programs were important determinants of interest. Arano et al (2004) found that nonindustrial private forest landowners who had participated in landowner assistance programs were more interested in participating in a proposed reforestation program for encouraging reforestation after harvest than were other landowners. Kramer and Jenkins (2009) found that farmers who were currently enrolled in a payment for ecosystem services program were more likely to be interested in future‐payment‐for‐ecosystem‐services programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests current or past experience with conservation programs were important determinants of interest. Arano et al (2004) found that nonindustrial private forest landowners who had participated in landowner assistance programs were more interested in participating in a proposed reforestation program for encouraging reforestation after harvest than were other landowners. Kramer and Jenkins (2009) found that farmers who were currently enrolled in a payment for ecosystem services program were more likely to be interested in future‐payment‐for‐ecosystem‐services programs.…”
Section: Discussionmentioning
confidence: 99%
“…These landowners may also be in a better position to invest in their property, and more able to afford program‐related cost‐share requirements (Gan et al 2005). We hypothesized that INCOME would be positively correlated with interest in endangered species habitat conservation contracts because wealthier landowners are more likely to be able to afford costs associated with incentive programs (Arano et al 2004) and better able to access program information sources (Nagubadi et al 1996). AGE was hypothesized to be negatively related to interest in an endangered species habitat conservation contact because older landowners may be less inclined to place their property in conservation programs (Langpap 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding ownership of a written forest management plan, our expectation was that possession of a plan will improve landowner knowledge of, and access to, relevant information about ecosystem services and available monetary incentives, and thus increase landowner interest in managing their forests for ecosystem services (Arano et al, 2004). However, results…”
Section: Discussionmentioning
confidence: 99%
“…This research was conducted in Mississippi, located in the southern United States, where most of the major economic sectors include agriculture and forestry (USDA Forest Service, 2009). Approximately 65% of Mississippi's land area (8 million ha) is forested (Londo and Auel, 2004) and family forest landowners own approximately 70% of the total forest land area (Arano et al 2004). The main forest types in Mississippi include hardwood and oak-pine forests (53%), pine forests (33%), and other forests (14%) (Southeast Mississippi Forest Inventory Report, 2006).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation